Temporal Variations in Reproduction, Growth, Condition Index and Some Population Parameters Ofperna Viridis (Linnaeus 1758) - Al Barwani, Said Mohamed (2007)
The aim of this study was to investigate the temporal reproductive cycle, growth rate, sex ratio, spat fall densities, condition index and population parameters of Perna viridis in Sebatu, Malacca.